Farmer participation in CAP agri-environment measures for biodiversity conservation in Triglav National Park, Slovenia - Irena Bertoncelj; Tanja Travnikar (Italian Review of Agricultural Economics (REA), 2024)
Conservation of biodiversity at the field, farm and landscape levels is one of the agroecological principles. In Europe low-intensity farming practices which promote farmland biodiversity are financially supported by different agri-environment measures as part of the rural development policy (under the Common agricultural policy - CAP). We examined farmer participation in agri-environment measures in 8 municipalities within Triglav National Park (TNP) in Slovenia, with a focus on a selection of nine biodiversity promoting measures, which were comparable between the 2007-2013 and 2014-2020 program periods. We detected relatively low interest in any CAP measures with only approximately half of the TNP farmland being registered within the national system. Participation of TNP farmers in nine biodiversity promoting agri-environment measures (AEMs) has shown an overall positive trend between the two CAP programmes, with the most popular measures being organic farming and livestock grazing on high-alpine pastures. However, availability of CAP funds did not stop the farmland abandonment and there were some indications of tourism activities competing with agricultural production. To maintain biodiversity promoting agricultural practices in TNP in the future it will be important to implement agri-environmental measures with sufficiently high payments.
Keywords: Q1; Q5; 330; agri-environment measures; Agroecology transition; biodiversity conservation; protected areas